Growth rate, feed intake and feed utilization of Small East African goats supplemented with Leucaena leucocephala - Mtenga, L.A.; Shoo, R.A. (Elsevier, 1990)
Growth and digestibility studies were conducted with grazing indigenous Tanzanian goats on different levels of supplementation of Leucaena leucocephala. Four treatments were hay only (H), hay and 100 g leucaena (HL1), hay and 200 g leucaena (HL2) and hay plus leucaena ad libitum (HL3) in the growth study; and hay only (H), hay and 100g leucaena (HL1), hay and 200g leucaena (HL2) and leucaena only (L) in the digestibility study. Supplemented goats had higher growth rate (P